KONSEP DIYAT SEBAGAI SOLUSI KESEJAHTERAAN KELUARGA KORBAN PEMBUNUHAN DAYA PAKSA (OVERMACHT) PERSPEKTIF MAQASHID SYARIAH - Iqbal , M (IBLAM LAW REVIEW, 2021)
In discussing criminal liability, we will talk about the perpetrator of a criminal act, namely someone who has committed an act that is expressly prohibited and threatened with criminality by law, ideally that person should be convicted or punished. Likewise, the perpetrators of murder are threatened with imprisonment in accordance with the provisions of the Criminal Code. However, the perpetrators of criminal acts are not always punished because the Criminal Code provides several reasons that can erase a person's guilt so that they are free from all punishments. One of them is coercive power which is regulated in Article 48 of the Criminal Code. However, the problem is that there is no formulation of coercion in the Criminal Code so that judges in deciding cases of murder due to coercion are only based on the judge's considerations and beliefs. Islamic law in comparing the existing arrangements in the Criminal Code is because Islam prioritizes protection and compensation charged to the perpetrator against the family of the murder victim, both intentional and unintentional murder. Meanwhile, the existing criminal policies in the Criminal Code have not met the principles of legal certainty and a sense of justice in society. The concept of Diyat is a welfare solution for the families of victims of murder by force, because this sanction provides benefits that can have an impact on the future. This is what is called maqshid sharia, where the law was created aiming to maintain 5 things, namely religion, reason, soul, lineage, and treasure. And the concept of diyat at least maintains 2 things, namely descent and treasure.